發明的自我效能與認知好奇心對持續參與IEYI臺灣選拔賽意圖之研究 Relationship Between Self-Efficacy of Invention, Epistemic Curiosity, and Students' Intentions to Consistently Participate in the IEYI - 宋修德 Hsiu-Te Sung; 林意珊 Yi-Shan Lin (National Taiwan Normal University, 2021)
在21世紀的現今，創造力最大的成功關鍵即是擁有好的教育，當學生面臨競爭時，可以使他們更有動力去創造與學習。特別是當學生為了要解決創作過程中所產生的問題，需要發揮他們對於知識的求知欲時，認知好奇心為關鍵的因素。本研究希冀藉由發明自我效能與認知好奇心對持續參與IEYI臺灣選拔賽意圖的研究，瞭解發明自我效能影響認知好奇心的作用，反映到持續參與意圖（IEYI臺灣選拔賽），並透過認知好奇心介入學生的發明自我效能與持續參與意圖來確定該途徑的有效性。本研究選擇臺灣參與IEYI臺灣選拔賽之學生為對象，採便利抽樣法進行問卷調查，回收有效問卷745份。所得資料經AMOS 20結構方程模式進行驗 證性因素分析，結果顯示發明自我效能對I型認知好奇心（I type Epistemic Curiosity, IEC）與D型認知好奇心（D type Epistemic Curiosity, DEC）有極顯著正相關，IEC與DEC對持續參與均有顯著正相關。研究顯示，透過兩種認知型好奇心可以促進或抑制參與者的持續參與意圖， 增加了我們對認知型好奇心的認識，學生的認知好奇心可以在參與競爭的過程中，產生更高的持續參與意圖。 In the 21st century, creativity is the key to success and a vital component of quality education. Introducing an element of competition into education can motivate students to be more creative. Moreover, students should be encouraged to solve problems through creative processes and stimulate their pursuit of knowledge. Learning to be curious is a crucial factor in the creative process. This study investigated the relationship between self-efficacy of invention, epistemic curiosity, and students' intentions to consistently participate in the IEYI and understand the role of epistemic curiosity increasing self-efficacy and reflecting the intentions for consistent participation in the IEYI Taiwan trial. Through the intervention of epistemic curiosity, determine the effectiveness of this approach. This study selected Taiwan to participate in the IEYI Taiwan trial. A convenient sampling method was used to conduct a questionnaire survey for students, and 745 valid questionnaire responses were collected. The data obtained were analyzed using AMOS (version 20) structural equations for confirmatory factors. The results showed that the self-efficacy of invention had a significant positive correlation with I-type Epistemic Curiosity (IEC) and D-type Epistemic Curiosity (DEC). IEC and DEC continued to participate in the study. There is a significant positive correlation. This study demonstrated that the participants' intentions to consistently participate can be promoted or inhibited by either IEC or DEC, and our relationship with epistemic curiosity is increased. Students' epistemic curiosity can be enhanced through competition; hence, participants can arouse there consistent participation intention.